1998
DOI: 10.1046/j.1365-2281.1998.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐body cooling increases plasma endothelin‐1 levels in women with primary Raynaud's phenomenon

Abstract: To understand better the role of endothelin-1 (ET-1) in the pathogenesis of primary Raynaud's phenomenon (PRP), we investigated the basal ET-1 plasma levels and changes after whole-body cooling in healthy women and those with PRP. The study was performed as an open parallel-group comparison during the month of February. The Raynaud group included 21 female patients (mean age 45.3 years, range 21-57 years) who had had disabling Raynaud's phenomenon for a mean period of 17 years (range 2-26 years). The control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…However, chronic exposure to cold did not alter plasma levels of ET-1. This is in contrast with acute cold exposure (minutes or hours) which increases plasma ET-1 levels (59,60). It should be emphasized that ET-1 is produced in endothelial cells and predominantly secreted toward the adjacent VSMC, supporting the notion that ET-1 is an autocrine/paracrine agent rather than a circulating hormone.…”
Section: Cold Exposure and The Endothelin Systemmentioning
confidence: 94%
“…However, chronic exposure to cold did not alter plasma levels of ET-1. This is in contrast with acute cold exposure (minutes or hours) which increases plasma ET-1 levels (59,60). It should be emphasized that ET-1 is produced in endothelial cells and predominantly secreted toward the adjacent VSMC, supporting the notion that ET-1 is an autocrine/paracrine agent rather than a circulating hormone.…”
Section: Cold Exposure and The Endothelin Systemmentioning
confidence: 94%
“…Leppert et al [53] found that women with RP had increased levels of endothelin-1 after whole body cooling compared with age-matched, healthy controls. In contrast, Smyth et al [54] found no difference between baseline plasma and endothelin-1 levels in subjects with RP compared with controls.…”
Section: Hemostatic Factorsmentioning
confidence: 99%
“…A primary outcome of these mechanisms is the initiation of endothelium dysfunction, which appears central (perhaps as a result of or in combination with oxidative stress and inflammation) to further development of CVD. Evidence suggests a strong association between endothelium dysfunction and cardiovascular events, leading to high morbidity and mortality from CVD [36] as well as other disease states [3742]. Endothelium dysfunction is characterized by an imbalance between the dilator and constrictor forces in the vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…As with CVD, the vasoconstrictive effect of ET-1 is the proposed major cause of these conditions. In the extremities, cold-temperature-induced increases in ET-1 contribute to the pathogenesis of Raynaud's phenomenon [37, 100], in which exaggerated vasoconstriction causes discomfort (ischemic pain) and discoloration of the affected areas. Likewise, ET-1-related vascular dysfunction in the eye leads to intraocular inflammation; this plays an important part in the development of primary open-angle glaucoma [41].…”
Section: Introductionmentioning
confidence: 99%